2010
DOI: 10.1093/jopart/muq027
|View full text |Cite
|
Sign up to set email alerts
|

Judicial Review Litigation as an Incentive to Change in Local Authority Public Services in England and Wales

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…using equality to inform that. Interview 1Judicial reviews can offer clarity to decision makers tasked with implementing decisions while at the same time being unhelpful to those higher in the system who are responsible for decisions about resource allocation (Platt et al, 2010). Research has shown that an increase in the numbers of judicial reviews targeted at a public authority 'may drive improvements in local authority performance, as measured by official indicators' (Sunkin, 2015: 247).…”
Section: Results Of Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…using equality to inform that. Interview 1Judicial reviews can offer clarity to decision makers tasked with implementing decisions while at the same time being unhelpful to those higher in the system who are responsible for decisions about resource allocation (Platt et al, 2010). Research has shown that an increase in the numbers of judicial reviews targeted at a public authority 'may drive improvements in local authority performance, as measured by official indicators' (Sunkin, 2015: 247).…”
Section: Results Of Challengesmentioning
confidence: 99%
“…However, a participant in the study who advises local authorities on fulfilling their PSED said that after an earlier judicial review of a local authority’s round of funding cuts, they were now trying to implement the necessary cuts in line with a proper consideration of equality impact issues:So [local authority] is making a whole range of funding cuts and we’re making sure that there is equality analysis fitting into that, which is obviously going to mitigate risk of legal challenge for the council through judicial review, but also to make sure that those services that are maintained are not discriminating, so services aren’t being cut for the most disabled people, and services are going to be maintained for those where the need is greatest, really…using equality to inform that. (Interview 1)Judicial reviews can offer clarity to decision makers tasked with implementing decisions while at the same time being unhelpful to those higher in the system who are responsible for decisions about resource allocation (Platt et al, 2010). Research has shown that an increase in the numbers of judicial reviews targeted at a public authority ‘may drive improvements in local authority performance, as measured by official indicators’ (Sunkin, 2015: 247).…”
Section: Results Of Challengesmentioning
confidence: 99%
“…One of the most influential-and most controver sial (see, e.g., Schultz, 1998)-judicial impact studies is Rosenberg's (1991) Other studies have also focused more explicitly on issues of administrative justice, by studying the impact of judicial review on administrative agencies (see, e.g., Halliday, 2004;Hertogh and Halliday, 2004). Both Richardson (2004) and Platt, Sunkin, and Calvo (2010) present an overview of some of the most important research in this field in the UK. Also, Sunkin (2004) has identified a number of conceptual issues in researching the bureau cratic impact on judicial review.…”
Section: Impact Of the Courtmentioning
confidence: 99%
“…Out-of-court settlements can be extremely successful, 31 and in the right scenario court rulings can in£uence the way bureaucracies behave in the future. 32 Likewise, most of the ombudsmen have gone out of their way to publicise their work in a way which informs public bodies of what counts as good administration. 33 There remains an argument, therefore, that the ombudsman can make a di¡e-rence and can have a real in£uence, yet in the theoretical section of the book, the potential contributions and impact of di¡erent redress mechanisms on decisionmaking receive little scrutiny.…”
Section: Underexplored Perspectivesmentioning
confidence: 99%